Tourist micro entrepreneurship and business network: Basis for modelling: The case of Ecuador [Microemprendimiento Turístico y Tejido Empresarial Bases para una modelización: El caso de Ecuador] - Rojas Toledo, D. (2016)
This paper analyzes the specialization and location of Ecuadorian micro entrepreneurship and particularly the province of Loja, in order to get a characterization of the tourist micro entrepreneurship to strengthen this activity through business networks. This research applies the Gini coefficient as a measure of the specialization and location degree of tourist activity obtained using as a variable the employed population of the database of the Ministry of Tourism. The results show that the province of Guayas and Galapagos have different tourist structures from the rest of the country. With regard to the location, tourist transport sectors and food and beverage stand out as concentrated activities and with options to generate business network in tourism entrepreneurship.